Knowledge on Hepatitis B among Secondary Level Students at Birtamode, Jhapa - Khadka, Babita; Basnet, Saraswati (Journal of Research and Development, 2022)
Hepatitis B is a silent epidemic as it is a potentially life-threatening liver infection caused by the hepatitis B virus (HBV) and a major global health problem. The aim of this study was to assess the level of knowledge on hepatitis B among secondary level students at Birtamode, Jhapa. Descriptive cross-sectional research design was used. Non-Probability purposive proportionate sampling technique was used. Total sample size was 166 respondents. Self-developed, self-administered and semi-structured questionnaire was used for collecting a data. Descriptive and inferential statistics was used for analyzing the study. The findings of the study showed that the mean age of respondents was 14.52 years in which 57.8% were male. Similarly, 55.4% students were from grade 9 and 44.6% were from grade 10. Almost all (93.4%) of respondents mentioned book as major source of information. Among the studied respondents, 12.6% had good knowledge, 47% had fair knowledge and 40.4% had poor knowledge on hepatitis B. The level of knowledge was associated with study grade of respondents (p=0.007). The study concludes that fair level of knowledge regarding hepatitis B among respondents and level of knowledge was significant with study grade and almost of respondents gained information from book.